The Safety of Dronabinol and Nabilone: A Systematic Review and Meta-Analysis of Clinical Trials - Ákos Bajtel; Tivadar Kiss; Barbara Tóth; Szabolcs Kiss; Péter Hegyi; Nóra Vörhendi; Boglárka Csupor-Löffler; Noémi Gede; Judit Hohmann; Dezső Csupor (MDPI AG, 2022)
Dronabinol, a natural cannabinoid, and its semi-synthetic derivative, nabilone, are marketed as medicines in several countries. The aim of our work was to systematically evaluate the frequency of adverse events related to dronabinol or nabilone treatment compared to placebo. Scientific databases were searched for placebo-controlled clinical studies of patients receiving either dronabinol or nabilone therapy with placebo control groups. This meta-analysis was reported following the PRISMA guidelines using the PICO format, and it was registered with the PROSPERO register. There were 16 trials included in the meta-analysis. In the nabilone studies, drowsiness was more than 7 times as frequent in patients treated with nabilone than in the placebo group (OR: 7.25; 95% CI: 1.64-31.95), and the risk of dizziness (OR: 21.14; 95% CI: 2.92-152.75) and dry mouth was also higher (OR: 17.23; 95% CI: 4.33-68.55). The frequency of headache was not different in the two groups. In case of dronabinol, the frequency of dry mouth (OR: 5.58; 95% CI: 3.19-9.78), dizziness (OR: 4.60 95% CI: 2.39-8.83) and headache (OR: 2.90; 95% CI: 1.07-7.85) was significantly higher in the dronabinol groups, whereas in case of nausea, drowsiness and fatigue there was no difference. The severity of adverse events was typically mild-to-moderate and transient. In a risk-benefit assessment, these adverse effects are acceptable compared to the achievable benefit. However, considering the diversity of the adverse effects, more studies are needed to provide a more accurate assessment on the side effect profiles of these two compounds.